Integrated biosynthesis of the lignan (-)-pluviatolide in resting and growing E. coli cells - Knöfel, Ronja; Barsig, Jonas; Bechtold, Philipp A.; Günes, Cigdem; Luelf, U. Joost; Urlacher, Vlada B. (Frontiers in Bioengineering and Biotechnology, 2026)
Lignans exhibit a wide range of useful bioactivities. A key intermediate in their biosynthesis in plants is (−)-pluviatolide, which directs the pathway towards various high-value lignans like (−)-podophyllotoxin - the precursor of the clinically relevant antitumor drugs etoposide and teniposide. In an attempt to develop more sustainable ways for the production of lignans, which are traditionally isolated from plants, we previously established a heterologous biosynthesis of (−)-pluviatolide in Escherichia coli, in which recombinant genes were expressed from multiple plasmids. In this study, the genes encoding the four-enzyme, four-step reaction cascade from (+)-pinoresinol to (−)-pluviatolide were integrated into the chromosome of E. coli C41(DE3). The plasmid-based and plasmid-free E. coli strains were compared in resting and growing cell approaches. The performance of the plasmid-free recombinant system was similar to that of the plasmid-based system, regardless of the approach tested. The addition of glycerol and glucose as energy and carbon sources enhanced the productivity towards (−)-pluviatolide. LC-MS analysis revealed complete conversion of the substrate (+)-pinoresinol and the formation of (−)-pluviatolide with 99% product ratio in resting cells and 92% in growing cells.